Analysis Determinants Of Investment Interest In Sharia Securities Crowdfunding Platforms - Nugroho, Amal Fathullah; Supriyanto, Trisiladi; Tanjung, Hendri (Jurnal Ekonomi, 2024)
Specific research regarding sharia Securities Crowdfunding (SCF) platforms , because researchers have only found studies that discuss sharia fintech and sharia crowdfunding . SCF is not yet known in the community because it is still relatively new. This research aims to analyze the determinants of investment interest among the public in investing in sharia securities crowdfunding (SCF) platforms using analysis through the TPB and TAM models. This research uses a quantitative descriptive research approach with a survey method to obtain data directly from the field. The analysis method used is SEM-PLS which aims to test the relationships between model variables and between indicators and their constructs, as well as the relationships between constructs. The result is that the TPB and TAM models do not have a significant positive effect on investment interest in the sharia SCF platform. The Use of Technology model has a significant positive effect, only the SI indicator does not have a significant positive effect on investment interest in the sharia SCF platform. Sharia Compliance with knowledge indicators does not have a significant positive effect. conversely, the confidence indicator has a significant positive effect on investment interest in the sharia SCF platform. The fact is that Sharia SCF is a relatively new investment alternative, so there needs to be more outreach from all policy stakeholders, both the government, sharia SCF companies, and the public who want to invest in sharia SCF. The recommendation is to more intensively socialize SCF sharia so that it is known to the public from various aspects.